Seasonal influenza vaccine uptake in Germany 2007/2008 and 2008/2009: Results from a national health update survey - Böhmer, Merle M.; Walter, Dietmar; Müters, Stephan; Krause, Gérard; Wichmann, Ole (Vaccine, 2011)
In 2008/2009 a nationwide cross-sectional telephone survey was conducted to assess, among other health-relevant parameters, seasonal influenza vaccination coverage. Data from 21,262 household-interviews representative of the adult population in Germany were collected and analyzed. In seasons 2007/2008 and 2008/2009, vaccine uptake in individuals aged ≥60 years was 57% and 55% and in individuals with underlying chronic diseases 44% and 42%. Living in the eastern part of Germany, higher age, and medium household income level were independently associated with higher vaccine uptake in both target groups. Healthcare workers were significantly less frequently (21.9% in 2007/2008; 20.4% in 2008/2009) vaccinated than the general population (30.8% and 28.1%). Special effort must be undertaken to develop immunization strategies for improved vaccine uptake in target groups, especially in healthcare workers.